PENGARUH PENGGUNAAN CHAT GPT DALAM PEMBELAJARAN TERJEMAH INDONESIA-ARAB - Nurfaiza, Nurfaiza (STAI Nurul Huda Kapongan Situbondo, 2024)
The rapid advancement of technology has significantly influenced translation learning methods, particularly with the emergence of innovative tools such as Chat GPT (Generative Pre-trained Transformer). This study aims to explore the impact of Chat GPT on the quality and efficiency of Indonesian-Arab translation learning. A mixed-methods approach was employed, involving quantitative assessments of students' translation skills before and after the integration of Chat GPT in their learning process. Qualitative data were collected through interviews and surveys to gauge students' perceptions of using Chat GPT as a learning tool. The findings indicate a marked improvement in students' translation abilities, with enhanced accuracy and fluency in both Indonesian and Arabic. Participants reported increased engagement and motivation when utilizing Chat GPT, highlighting its effectiveness in facilitating communication and understanding in translation tasks. The study underscores the potential of Chat GPT as a transformative tool in language education, offering a novel approach to overcoming challenges in translation learning. It also emphasizes the need for further research to compare the effectiveness of Chat GPT with traditional teaching methods. This research contributes valuable insights into the integration of AI technology in language education, suggesting that Chat GPT can significantly enhance the learning experience for Indonesian-Arab translation students. Future studies should focus on longitudinal assessments and broader comparative analyses to fully understand the implications of AI in translation pedagogy